Analysis of Genetic Variation of Ganoderma sp. as an Initial Step in Controlling Palm oil Basal Stem Rot Disease - Achmad Himawan (LPPM UNIVERSITAS ISLAM KUANTAN SINGINGI, 2025)
Basal stem rot (BSR) disease caused by Ganoderma spp., particularly Ganoderma boninense, represents a major threat to the sustainability of Indonesia's oil palm industry, resulting in productivity losses of 50-80%. High genetic variation among pathogens constitutes a primary obstacle in developing effective control strategies. This study aimed to analyze the genetic variation in Ganoderma as a preliminary step toward controlling basal stem rot in oil palm using ITS region DNA sequencing with ITS1 and ITS4 primers. Three Ganoderma sp. isolates were used: code 1 from the Biotechnology Laboratory of Lampung University, code 2 from the Plant Pest and Disease Laboratory of Gadjah Mada University, and code 3 from an online store. DNA extraction was performed using the TIANGEN Plant Genomic DNA Kit; PCR amplification with ITS1-ITS4 primers; and the PCR products were sequenced and analyzed using BioEdit and NCBI BLAST. Results showed that isolates code 1 and code 2 were identified as Ganoderma boninense, while isolate code 3 was contaminated with Fusarium sp. Alignment analysis using BioEdit confirmed extremely high genetic variation between the two G. boninense isolates with extensive nucleotide polymorphisms. This significant intraspecific diversity indicates the complexity of basal stem rot pathogen populations and emphasizes the importance of molecular approaches for accurate characterization. These findings provide a scientific foundation for developing more effective and adaptive control strategies and support oil palm resistance breeding programs based on representative pathogen genetic characteristics.